2016
DOI: 10.1016/j.preghy.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pregnancy hypertensive disorders in Mongolia

Abstract: Objective To estimate the prevalence of preeclampsia in a contemporary population of Mongolian women living in urban and rural areas. We determined the sensitivity and specificity of diagnosis based on established diagnostic criteria and assessed whether local diagnostic criteria were similar to those used in the US. Study Design Cross-sectional study of urban and nomadic pregnant women recruited in Ulaanbaatar (n=136) and rural provinces (n=85). Main Outcome Measures Preeclampsia defined as hypertension n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…The prevalence of preeclampsia and eclampsia among all deliveries were 2.2% and 0.7% respectively which is consistent with the 2.13 % for preeclampsia in Iran [20] but lower than the finding in Mongolia where by researchers reported 4.1% prevalence of preeclampsia [27]. The 0.7% prevalence of eclampsia in this study is higher than the one reported in Iran (0.03%) [20].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of preeclampsia and eclampsia among all deliveries were 2.2% and 0.7% respectively which is consistent with the 2.13 % for preeclampsia in Iran [20] but lower than the finding in Mongolia where by researchers reported 4.1% prevalence of preeclampsia [27]. The 0.7% prevalence of eclampsia in this study is higher than the one reported in Iran (0.03%) [20].…”
Section: Discussionsupporting
confidence: 86%
“…Pregnant women in Mongolia were found to have preeclampsia rates of about 4% (4.4% in Ulaanbaatar and 3.5% in rural regions) [101]—an important risk factor for preterm birth and low birth weight [102]. A meta-analysis involving 21 studies reported that low vs. high maternal 25(OH)D concentration was associated with an OR of 1.62 (95% CI, 1.36 to 1.94) for preeclampsia [75], the OR for the Asian sub-population being 2.07 (95% CI, 1.51 to 2.85).…”
Section: Resultsmentioning
confidence: 99%
“…Expected weekly counts for key pregnancy outcomes such as low birth weight (4.5% of births), pre-eclampsia (4.1% of pregnancies) and spontaneous abortion (5% of pregnancies) in Ulaanbaatar are 35, 32 and 38, respectively, based on country-specific data. [25][26][27] Furthermore, considering the introduction of the pneumococcal vaccine in July 2016, historic data on seasonal pneumonia patterns in Mongolia and the latest Mongolian Multiple Indicator Cluster Survey data on child acute respiratory infection presentation, it is estimated that child under 5 respiratory admission rates will range between 2% and 10% for the summer and winter months, respectively. 21 28 29 Air quality assessment As a measure of Ulaanbaatar's air quality over the study period, routinely collected air pollution measurements of PM 2.5 , PM 10 , carbon monoxide, SO 2 , NOx and ozone concentrations (µg/m 3 ) will be obtained from the 17 air quality monitoring stations run by the GoM as well as one US Embassy air measurement station in Ulaanbaatar.…”
Section: Study Populationmentioning
confidence: 99%